Body representation underlies response of proprioceptive acuity to repetitive peripheral magnetic stimulation - Xia, Yunxiang; Tanaka, Kento; Yang, Man; Izumi, Shinichi (Frontiers in Human Neuroscience, 2022)
Proprioceptive acuity is of great significance in basic research exploring a possible neural mechanism of fine motor control and in neurorehabilitation practice promoting motor function recovery of limb-disabled people. Moreover, body representation relies on the integration of multiple somatic sensations, including proprioception that is mainly generated in muscles and tendons of human joints. This study aimed to examine two hypotheses: First, different extension positions of wrist joint have different proprioceptive acuities, which might indicate different body representations of wrist joint in the brain. Second, repetitive peripheral magnetic stimulation (rPMS) applied peripherally to the forearm radial nerve and extensors could change proprioceptive acuity at the wrist joint. Thirty-five healthy participants were recruited then randomly divided into the real stimulation group (n = 15) and the sham stimulation group (n = 20). The participants’ non-dominant side wrist joint position sense was tested at six extension positions within the physiological joint motion range (i.e., 10°, 20°, 30°, 40°, 50°, 60°) both before stimulation and after stimulation. Results showed that proprioceptive bias (arithmetic difference of target position and replicated position) among six extension positions could be divided into lower-extension position (i.e., 10°, 20°, 30°) and higher-extension position (i.e., 40°, 50°, 60°). One session rPMS could influence proprioceptive bias in lower-extension position but not in higher-extension position. However, proprioceptive precision (standard deviation within lower-extension position and higher-extension position) was not influenced. To conclude, proprioceptive bias may vary between different wrist extension positions due to different hand postures being related to changes in body representation, and different functions relating to proprioceptive bias and proprioceptive precision may underlie two aspects of body representation.